Kegiatan Aktualisasi Nilai Pancasila dalam Proses Pembelajaran Sekolah Dasar Negeri 050 Cibiru Kota Bandung - Dio Ramadhan; Reysheeka Kayla Fitriani Adriansyah; Femi Chantika Putri; Salwa Marsyadina; Susan Salsabila; Dendi Tegar Deristianzah; Muhammad Ikhwan Hanif; Angka Wijaya Eka; Miqdar Shibghotullah; Hanif Muwahhid Maris; Dian Herdiana (Yayasan Daarul Huda Kruengmane, 2026)
The cultivation of Pancasila values from elementary school is a strategic step in shaping the character of the nation’s future generation. This study aims to describe how activities that promote Pancasila values are implemented through game-based learning for fifth-grade students at SD Negeri 050 Cibiru, Bandung City. The method used is Classroom Action Research (CAR) with a qualitative approach focused on internalizing the values of Divinity, Humanity, and Unity. Learning activities included lectures, discussions, Q&A sessions, contextual learning, and role-play, which allowed students to actively and practically engage in understanding each principle. The results indicate that the game-based learning model can boost students’ confidence in sharing opinions, foster tolerance, appreciate differences, and practice mutual cooperation during class activities. Additionally, students showed high enthusiasm and were able to connect Pancasila values to everyday life. Therefore, game-based learning is effective in reinforcing understanding and appreciation of Pancasila values among elementary students and can be recommended as an alternative method in character education.